Actin-dependence of the chloroplast cold positioning response in the liverwort Marchantia polymorpha L. - Kimura, Shun (PeerJ, 2016)
The subcellular positioning of chloroplasts can be changed by alterations in the environment such as light and temperature. For example, in leaf mesophyll cells, chloroplasts localize along anticlinal cell walls under high-intensity light, and along periclinal cell walls under low-intensity light. These types of positioning responses are involved in photosynthetic optimization. In light-mediated chloroplast positioning responses, chloroplasts move to the appropriate positions in an actin-dependent manner, although some exceptions also depend on microtubule. Even under low-intensity light, at low temperature (e.g., 5°C), chloroplasts localize along anticlinal cell walls; this phenomenon is termed chloroplast cold positioning. In this study, we analyzed whether chloroplast cold positioning is dependent on actin filaments and/or microtubules in the liverwort Marchantia polymorpha L. When liverwort cells were treated with drugs for the de-polymerization of actin filaments, chloroplast cold positioning was completely inhibited. In contrast, chloroplast cold positioning was not affected by treatment with a drug for the de-polymerization of microtubules. These observations indicate the actin-dependence of chloroplast cold positioning in M. polymorpha. Actin filaments during the chloroplast cold positioning response were visualized by using fluorescent probes based on fluorescent proteins in living liverwort cells, and thus, their behavior during the chloroplast cold positioning response was documented.